HUBUNGAN PERILAKU MEROKO KELUARGA DI DALAM RUMAH TANGGA DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA BALITAi Wilayah Kerja Puskesmas Rasau Jaya - Siti Oktaviani; Fitri Fujiana; Titan Ligita (Universitas Bengkulu, 2022)
Background: Acute Respiratory Tract Infection (ARI) the main trigger of toddlers mortality which is in the highest position in the under-five rate. People who have exposed to secondhand smoke are more likely to have health problems than people who smoke. Environment that contains a lot of cigarette smoke can make Toddlers suffer from ARI. Objective: To determine the relationship between family smoking behavior in the house and the incidence of acute respiratory infections (ARI) in children under five in the Work Area of the Rasau Jaya Health Center. Method: This study was an observation Cross Sectional. Using non-probability purposive sampling technique of 60 respondents. Using a smoking behavior questionnaire instrument which was filled out by the respondents. Statistical test using Chi-Square test. Results: Statistical test results showed that 38 out of 60 toddlers are suffer from ARI with 32 are caused by smokers who do not pay attention to the surrounding environtment, 23 are caused by the number of moderate smokers, 32 are caused by the number of moderate cigarette, and 32 are caused by smoking behavior in the house with p-Value <0.05. Conclusion: There is a significant relationship between the type of smoker, family members of smokers, smoking habits, smoking location with the dependent variable on the incidence of ARI among children under five at the Rasau Jaya health center.Keywords: Toddler, SPH Behavior, ARI.